1985
DOI: 10.1159/000457058
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Disposition in Newborn Lambs and Comparison of Alcohol Dehydrogenase Activity in Placenta and Maternal Sheep, Fetal and Neonatal Lamb Liver

Abstract: The kinetic disposition of ethanol was studied in neonatal lambs. The mean plasma clearance rate was 36 mg/l/h, 17% of that in near-term pregnant sheep. Activity increased slowly during the first 5 days of life. Hepatic alcohol dehydrogenase activity in the neonatal lamb was only 7% of that in adult sheep, but was similar to activity in the near-term fetus. Placental enzyme activity was even lower than that in the fetus and neonate, suggesting only a minor role for it in the metabolic disposition of ethanol du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Previous studies in foetal lambs have shown transient tachycardia but no consistent blood pressure changes (Ayromlooi et al, 1979;Cook et al, 1981). Those results may be accounted for by the significantly lower ethanol metabolic rate in foetal and newborn lambs (Cumming et al, 1985) compared to newborn humans (Wagner et al, 1970;Fuchs & Fuchs, 1981) and piglets (Chandler et al, 1989).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies in foetal lambs have shown transient tachycardia but no consistent blood pressure changes (Ayromlooi et al, 1979;Cook et al, 1981). Those results may be accounted for by the significantly lower ethanol metabolic rate in foetal and newborn lambs (Cumming et al, 1985) compared to newborn humans (Wagner et al, 1970;Fuchs & Fuchs, 1981) and piglets (Chandler et al, 1989).…”
Section: Discussionmentioning
confidence: 90%
“…Although the adverse effects of chronic ethanol exposure on the foetus (Jones et al, 1974;Hanson et al, 1976) are well characterized, the effects of acute ethanol intoxication on the newborn are still unclear. Previous studies in foetal and newborn lambs, as far as mean arterial blood pressure (MABP) and heart rate (HR) are concerned, have produced conflicting results (Mann et al, 1975;Ayromlooi et al, 1979;Cook et al, 1981;Cumming et al, 1985). Previously, we have found that newborn piglets have rates of ethanol metabolism close to those reported for human neonates (2.0 + 0.2 mmol I -1 h '), and that acutely intoxicated piglets develop significant hypotension and tachycardia which can be reversed by blocking ethanol metabolism with 4methylpyrazole (4-MP) (Chandler et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…15] and not increased by ethanol administration [15]. and in near-term sheep fetuses and neonatal lambs only 10 and 7% of that in the mother [3]. Also alcohol dehydrogenase activity in rat fetuses was absent in 15-day fetuses and low in 21-day fetuses [22], These observations, as well as the present mor phometric data, also agree with the previously described morphologic changes (abnormal mitochondrial shape and size, disorientation of cristae and accumulation of paracrystalline material, and aggregation of endoplasmic cis ternae) [18.…”
Section: Discussionmentioning
confidence: 99%